Athletic performance decreases in young basketball players after sitting - Alberti, G.; Annoni, M.; Ongaro, L.; Scurati, R.; Michielon, G. (International Journal of Sports Science and Coaching, 2014)
The purpose of this study was to assess the effect of prolonged sitting on the vertical jump of young basketball players. After a standard warm-up of 15 minutes, players from five basketball teams underwent countermovement jump (CMJ) and stiff leg (SL) tests (T1 time point). The tests were repeated (T2 time point) after the participants spent 20 minutes under different conditions, one by each team: playing, sitting, standing, and active while sitting. Sitting players further resumed the activity for two minutes, after which the CMJ and SL tests were repeated. Neither the playing nor the standing players showed significant differences in vertical jump capacity between T1 and T2. After being seated for 20 minutes, the jump height decreased in all seated players. After workout resumption, the sitting players' jump height was only slightly lower and not significantly different than the post-warm-up condition. Sitting on the bench after warm-up decreases the performance.